Prerevolutionary historiographical sources of administrative and legal integration of the North Caucasus to Russia in the second half of the XIX – early XX centuries - Petr A. Kuzminov; Eldar Z. Tlostanov (Кавказология)
The article examines the legality of using pre-revolutionary authors’ works not only as historical but also as historiographical sources, drawing on materials from Russia’s administrative and legal policy in the North Caucasus in the second half of the nineteenth and early twentieth centuries. This approach opens up new avenues for extracting information from previously known scientific works, because, in addition to data on the topic under study, the historiographer considers the author’s personality, level of education, intelligence, literary quality of the text, the goals of the article or book, the concepts defended, the ideological positions of the publication/publisher’s editorial board, and so on. This approach expands the informative significance of the publications under study, helps to comprehend their place among other works on the research topic.The article assesses the study’s core concept – “historiographical source” – in regional and all-Russian historiography. The analysis of the potential of the materials presented in pre-revolutionary historiography allows the entire corpus of historiographical sources to be divided into several hierarchical groups: monographs (books), collections of documents, articles summarizing works, reviews, obituaries, reference materials, documents of local lore organizations, and so on. This article employs certain categories of historiographical sources.The viewpoint on dividing the pre-revolutionary periodical press into two major trends: officially protected and liberal democratic. The contribution of the most prominent scientists and local historians to the development of a historiographical tradition on the investigated topic is evaluated. Materials from the pre-revolutionary periodical press are revealed, containing information about the evolution of views and scientific concepts of a number of authors, which determine the sound of the problem under discussion, bear the imprint of time, and allow a closer look at the flavor of the era under study.